Răspuns:
[tex]1.1(6) = 1 \frac{16 - 1}{90} = 1 \frac{15}{90} = 1 \frac{1}{6} = \frac{7}{6} [/tex]
[tex]0.5 = \frac{1}{2} [/tex]
[tex]1 \frac{1}{4} = \frac{5}{4} [/tex]
[tex]0.(6) = \frac{6}{9} = \frac{2}{3} [/tex]
[tex]2 \frac{1}{4} = \frac{9}{4} [/tex]
[tex] \frac{1}{2} - \frac{5}{4} = - \frac{3}{4} [/tex]
[tex] \frac{2}{3} - \frac{9}{4} = - \frac{19}{12} [/tex]
[tex] - \frac{3}{4} + \frac{19}{12} = \frac{10}{12} = \frac{5}{6} [/tex]
[tex] \frac{7}{6} - \frac{5}{6} = \frac{2}{6} = \frac{1}{3} [/tex]
Răspuns b